Diagnóstico del potencial eólico en el sector Pusuchisí alto del cantón Latacunga, período 2011-2013, Propuesta de emplazamiento de un parque eólico. - Lucio Castro, Miguel Angel (2013)
This paper explains the theory behind the mathematical methods that quantify the potential for energy extraction for wind power wind, it is regarded as a clean energy source, with other renewable energy sources can minimize air pollution. The before mentioned mathematical methods evaluate the feasibility of the planned installation of a wind farm in the Alto Pusuchisi sector, designated to deliver energy to the company ELEPCO S.A. It details the principal generation systems, specifying the types of motor machines, and synchronous and asynchronous generators. The installation potential was determined using the criteria of 1/20 of the short circuit power in the connection point. A line diagram illustrates the connection between the towers with the new substation design and the existing towers in Central Illuchi 1. Measurements are calculated for the circuit breakers required to control and protect the system. Recommendations are given regarding potential improvements of the project and design.